Does the common labor market imply the need for a European public pension system? - Friedrich Breyer; Martin Kolmar (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
In a recent paper, Homburg and Richter have argued that with free mobility of labor within a common labor market there is a need to harmonize and even consolidate pay-as-you-go financed national public pension systems to reach an efficient allocation of labor. We show that with free and unrestricted mobility of labor there is no need for consolidation. In contrast, if mobility is restricted in such a way that fertility-caused differences in popula-tion growth cannot be equalized by migration, one gets a large variety of minimum coordination requirements for an efficient equilibrium.
Keywords: H55; H73; R23; 330; European integration; Public pension systems; Labor mobility; Gesetzliche Rentenversicherung; Arbeitsmobilität; Theorie; EU-Staaten; EU-Binnenmarkt